Otolith growth ring pattern of Monopterus albus Zuiew from swamp area of the Sawah Village, Kampar District, Riau - br. Damanik, Suci Anggeraini; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract            In the swamp area of the Sawah Village, the water quality is affected by pollutant originated from activities conducted around and in the swamp area.The low quality water may negatively affects the growth of Monopterusalbus and it is reflected in the growth pattern in the otolith of fish living in that swamp. A research aims to understand the pattern of otolith growth rings of theMonopterusalbuswas conducted in March to May 2018.The fish was captured using fishing gears, once/week. There were 61 fishes (31 females, 15 transitionand 15 males). The otoliths (sagita) is taken by tweezers and shaved using fine grindstone. Growth ring pattern in the otolith was studied using a binocular microscope. The length of otolith was 2.25-4.75 mm and weight 0.0040-0.0200 gram. Results shown that the  number of dark ring in the otolith of the fish ranged from 1 to 4. The distance between the nucleus and the first dark ring was varied (0.25-1.75 mm). These data indicates that the formation of dark ring may not be affected by periodical condition but it is affected by individual problem. The number of dark ring in otolith indicate that the fish is able to live properly in the swamp areas. Keywords: dark ring, sagita, freshwater eel, eel growth